Semantics, world view and Bible translation : an integrated analysis of a selection of Hebrew lexical items referring to negative moral behaviour in the book of Isaiah - Van Steenbergen, Gerrit Jan (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2002.